Рудные и рудоносные формации: терминологический справочник - Кулындышев В. А. Владимир Александрович; Соловьев В. А. Владимир Алиевич; Архипов Г. И. Геннадий Иванович; Воеводин В. Н.; Гаврилов В. И.; Косыгин Ю. А.; Кулиш Е. А. (Москва, Недра, 1983)
Сост. указаны на обороте тит. листа